Comparative study on the deposition of silicon oxide permeation barrier coatings for polymers using hexamethyldisilazane (HMDSN) and hexamethyldisiloxane (HMDSO). (15th May 2018) - Mitschker, F; Schücke, L; Hoppe, Ch; Jaritz, M; Dahlmann, R; de los Arcos, T; Hopmann, Ch; Grundmeier, G; Awakowicz, P
Abstract: The effect of the selection of hexamethyldisiloxane (HMDSO) and hexamethyldisilazane (HMDSN) as a precursor in a microwave driven low pressure plasma on the deposition of silicon oxide barrier coatings and silicon based organic interlayers on polyethylene terephthalate (PET) and polypropylene (PP) substrates is investigated. Mass spectrometry is used to quantify the absolute gas density and the degree of depletion of neutral precursor molecules under variation of oxygen admixture. On average, HMDSN shows a smaller density, a higher depletion and the production of smaller fragments. Subsequently, this is correlated with barrier performance and chemical structure as a function of barrier layer thickness and oxygen admixture on PET. For this purpose, the oxygen transmission rate (OTR) is measured and Fourier transformed infrared (FTIR) spectroscopy as well as x-ray photoelectron spectroscopy (XPS) is performed. HMDSN based coatings exhibit significantly higher barrier performances for high admixtures of oxygen (200 sccm). In comparison to HMDSO based processes, however, a higher supply of oxygen is necessary to achieve a sufficient degree of oxidation, cross-linking and, therefore, barrier performance. FTIR and XPS reveal a distinct carbon content for low oxygen admixtures (10 and 20 sccm) in case of HMDSN based coatings. The variation of interlayer thickness also reveals significantly higher OTR for HMDSO based coatings on PET and PP. Barrier performance of HMDSO based coatings improves with increasing interlayer thickness up to 10 nm for PET and PP. HMDSN based coatings exhibit a minimum of OTR without interlayer on PP and for 2 nm interlayer thickness on PET. Furthermore, HMDSN based coatings show distinctly higher bond strengths to the PP substrate.